Analysis Platelet Indices in Patient Type 2 Diabetes Mellitus with Vascular Complication - Nelly Tolla Taggara; Suci Aprianti; Darmawaty ER (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Type 2 Diabetes Mellitus(T2DM) is an endocrin disease that is marked by hyperglycemic condition due to a decrease increase in insulin secretion and insulin resistance or both. Indonesia is the 7th country with the highest incidence of diabetes mellitus in the world. Progression of the disease is slow and cause vascular endothelial damage. The increase of platelet indices is suspected to be an indications of vascular complications. To evaluate the platelet indices in diabetics patients with complication and correlate these indices with GDP and HbA1c. Analyzed platelet indices and biochemical data of patients seen in outpatients by clinicans of wahidin soedirohusodo hospitals. 120 patients with type 2 diabetes mellitus were included with 64 patients vascular complication and 56 patients without complication. Observed an increase in mean platelet volume (MPV): 9,96 + 1.99vs 8.87 + 1.35(p-value: 0,001); in platelet distribution width (PDW): 15.29 + 3.45 vs 12.36 + 2.819(p-value: 0,000; without increase plateletcrit (PCT); 0.28 + 0.14 vs 0.25 + 0.12 (p-value: 0.168). we observed a correlation between FBG with PDW (P=0.044). The study findings point to the significant differences in platelet indices (MPV and PDW) in patients with T2DM with complication and without complication, suggesting the presence of platelet in diabetics type 2 patients more reactive and aggregatable in this group of individuals. These suggest that platelet evaluation may be useful in the early detection of long term complication in diabetics patients.